2010
DOI: 10.1136/pgmj.2009.092775
|View full text |Cite
|
Sign up to set email alerts
|

Chronic viral hepatitis and chronic kidney disease

Abstract: Chronic kidney disease (CKD) has become a major public health problem worldwide over the past few decades because of the increasing prevalence of hypertension, diabetes mellitus, and elderly individuals in most countries. Chronic viral hepatitis (due to hepatitis B virus (HBV) and hepatitis C virus (HCV)) also poses significant morbidity and mortality globally. Both these viruses can cause CKD and these infections can occur as a consequence of CKD management. CKD patients acquiring HBV or HCV infection have hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 74 publications
(85 reference statements)
1
40
0
2
Order By: Relevance
“…hepatitis C virus; oxidative stress; antioxidants; pyrrolidine dithiocarbamate; glutathione peroxidase HEPATITIS C VIRUS (HCV) is one of the most important causes of chronic liver disease in the world (10). Chronic liver disease is the main cause of cirrhosis, liver failure, and liver cancer.…”
mentioning
confidence: 99%
“…hepatitis C virus; oxidative stress; antioxidants; pyrrolidine dithiocarbamate; glutathione peroxidase HEPATITIS C VIRUS (HCV) is one of the most important causes of chronic liver disease in the world (10). Chronic liver disease is the main cause of cirrhosis, liver failure, and liver cancer.…”
mentioning
confidence: 99%
“…It is thought that chronic viral hepatitis infl uences around 500 million people throughout the world (17,18). Increase in the prevalence of CKD, and high rates of HBsAg and Anti-HCV seropositivity seen in hemodialysis patients have rendered these infections important in CKD population.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in the prevalence of CKD, and high rates of HBsAg and Anti-HCV seropositivity seen in hemodialysis patients have rendered these infections important in CKD population. It is known that, in CKD, especially in patients receiving dialysis, and in renal transplant patients, HBV and HCV infections are independent causes of morbidity and mortality (17)(18)(19)(20)(21). The risk of the development of cirrhosis and hepatocellular carcinoma due to chronic HBV and HCV infections, the risk of transmission to the other patients and medical personnel in hemodialysis centers, and the necessity for close follow up in renal transplant patients during immunosuppressive treatment are the major problems associated with HBV and HCV infections.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have shown that chronic carriage of HBV in adult individuals may lead to the development of nephrotic syndrome, the commonest histological type being membranous nephropathy [11,12]. In total, the different morphological forms of HBV-associated renal injuries may include membranous nephropathy, membranoproliferative glomerulonephritis, mesangial proliferative glomerulonephritis, immunoglobulin A (IgA) nephropathy, focal segmental glomerulosclerosis, and polyarteritis nodosa [13].…”
Section: Renal Abnormalities In Hbv-infected Patientsmentioning
confidence: 99%